Women Archaeologists under Communism, 1917-1989 - Curta, Florin. author. aut Link
XII, 227 p.
Keywords: This book explores the uncharted territory of the history of archaeology under Communism through the biographies of five women archaeologists from the Soviet Union, Bulgaria, Romania, Hungary, and Poland. They were working in medieval archaeology, with a specific focus on the (early) Slavs. The choice of specialists in medieval archaeology has much to do with the fact that in the five East European countries considered in this book, medieval archaeology began to develop into a serious discipline less than a century ago. The main catalyst for the sudden rise of medieval archaeology was a dramatic shift in emphasis from traditional political and constitutional to social and economic history. In five countries, the rise of medieval archaeology thus coincides in time, and was ultimately caused by the imposition of Communist regimes. The five women were therefore true pioneers in their field, and respective countries. Florin Curta is Professor of Medieval History and Archaeology at the University of Florida, USA. His books include The Making of the Slavs (2001) and Slavs in the Making (2021). He is also the editor of several collections of studies. His most recent book is The Long Sixth Century in Eastern Europe (2021). Iurie Stamati teaches Historiography at the University of Quebec at Rimouski (Université du Québec à Rimouski), Canada. His research focuses on the political instrumentalization of history and archaeology in Eastern Europe. He is the author of several articles and of The Slavic Dossier: Medieval Archaeology in the Soviet Republic of Moldova Between State Propaganda and Scholarly Endeavor (2019).